Dampak Teknologi Gadget terhadap Perilaku Komunikasi Anak di Desa Tegal Arum - Maulana, Ade Novia; Putra, D.I Ansusa; Ariska, Intan Dea (JOSTECH: Journal of Science and Technology, 2021)
The research is motivated by the reality that pay attention and requires attention, namely about the factors that influence chidren to play such as lack of parenting styles, the environment, peers who also have a bad influence. It can be seen that the actual role of gadget technology is to send short massages and make work easier, but to the negligence of parents of early childhood, they have started to use gadgets and as a result it can have a negative impact on children’s mental and health. The research approach that the writer uses is descriptive qualitative research, with research methods of observation, interviews and documentation. In this study, it can be concluded that the continuous use of gadget media on children will have a negative impact on children, such as disruption of the nervous system, inhibition of child development and lack of social interaction in society. That is why the role of parents is needed for the child’s development process, parents must always guide and pay attention to their children while playing gadgets.